DESIGNING OF THE AUTHOR’S FASHION COLLECTION USING PATCHWORK TECHNIQU - Абрамова, О. В.; Єжова, О. В.; Чистякова, Л. О.; Кудревич, І. О. (Art and Design, 2020)
Research of design-design features of the creative collection of clothing using the technology of patchwork. Methodology. An integrated approach, historical analysis of the object of research, systematization of parochial species, method of combinatorial formation have been applied. Results. The design of the clothing collection was analyzed using the paintwork technique. The historical development of the technology of patchwork is considered. There has been an improvement in the type classification of the patchwork, which includes the types, seams and blocks of the art. The technology of execution of the units of the peach «flying geese» and «cut» is described. On the basis of the theoretical study carried out, an up-to-date collection of women ’s and men ’s clothing has been developed with the use of modern techniques of peachyard, as technologies of repeated application and processing of sewing wastes and textiles. The views, seams and blocks of the patchwork are systematized. The specifics and possible variants of modern paintings in the technology of patchwork and their application in the design-design of the collection of clothing models have been revealed. Practical significance. The possibilities of using modern varieties of patchwork in the creation of a collection of clothing have been demonstrated. Proposed is a technological method of making pachopper blocks according to templates using cutting with a disk knife and crease using a water-soluble stabilizer.